2005
DOI: 10.1038/sj.ejcn.1602242
|View full text |Cite
|
Sign up to set email alerts
|

The Chakaria food system study: household-level, case–control study to identify risk factor for rickets in Bangladesh

Abstract: Objective: A comprehensive, multiround survey of local food systems in a rickets-endemic area of Bangladesh was conducted to identify household-level risk factors for rickets. Design: A household-level, case-control study was conducted in a rickets-endemic area, Chakaria, with planned comparisons between households with one or more rachitic child and neighboring households with no affected children. Setting: A rickets-endemic area of southeastern Bangladesh, Chakaria. Subjects and methods: An interview-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
(22 reference statements)
3
26
2
Order By: Relevance
“…These findings are, however, comparable to those from previous studies examining Fe and Ca intake among Bangladeshi children (4,45,46) . Food intake data also revealed a lack of diversity in infant diets, with plant foods based on cereals, vegetables and fruits being the main items consumed.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are, however, comparable to those from previous studies examining Fe and Ca intake among Bangladeshi children (4,45,46) . Food intake data also revealed a lack of diversity in infant diets, with plant foods based on cereals, vegetables and fruits being the main items consumed.…”
Section: Discussionsupporting
confidence: 88%
“…Because leg signs are seen in only about 47% of cases [18], these results suggest an overall rickets prevalence approaching 4%. In Chakaria, we found that nearly one third of households had a rachitic child [20].…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, rickets has been reported in at least 21 countries including Bangladesh where it appears to be most prevalent in Cox's Bazar District of southeastern Bangladesh [18][19][20]. The Bangladesh Institute of Mother and Child Health reported that 9% of children examined in Chakaria sub-district presented with one or more rachitic signs including varus and valgus deformities of the knees, sabre tibiae, swollen wrists and joints, pectus carinum, and difficulty walking, with 11% of that number also showing active rickets elevated serum alkaline phosphatase (AP) activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence primarily from developing countries demonstrates that traditional diets low in calcium cause NR [30,43,69,93,[112][113][114] . Therefore, special diets during infancy such as those that avoid milk and dairy products, those using soy or rice milk that are not specifically designed for infants, and/or vegan and macrobiotic diets may predispose infants to NR [115][116][117][118][119][120] .…”
Section: Evidencementioning
confidence: 99%